2020
DOI: 10.1038/s41396-020-00768-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature transcends partner specificity in the symbiosis establishment of a cnidarian

Abstract: Coral reef research has predominantly focused on the effect of temperature on the breakdown of coral-dinoflagellate symbioses. However, less is known about how increasing temperature affects the establishment of new coral-dinoflagellate associations. Inter-partner specificity and environment-dependent colonization are two constraints proposed to limit the acquisition of more heat tolerant symbionts. Here, we investigated the symbiotic dynamics of various photosymbionts in different host genotypes under “optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 84 publications
(132 reference statements)
1
22
0
Order By: Relevance
“…In the second temperature experiment, it became clear that Breviolum minutum SSB 01 was much more susceptible to enhanced temperatures starting at 30 • C. This demonstrates different temperature thresholds between strains of B. minutum, also within the genus Breviolum the species-specific tolerances differ. This is in line with another study, where closely related Breviolum species revealed significant functional variation against elevated temperature (Bayliss et al, 2019;Herrera et al, 2020). The different genotypes exhibited decreasing photosynthetic activity at elevated temperatures, which could be an important feature for the strength of the relationship between the symbiont and the host.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the second temperature experiment, it became clear that Breviolum minutum SSB 01 was much more susceptible to enhanced temperatures starting at 30 • C. This demonstrates different temperature thresholds between strains of B. minutum, also within the genus Breviolum the species-specific tolerances differ. This is in line with another study, where closely related Breviolum species revealed significant functional variation against elevated temperature (Bayliss et al, 2019;Herrera et al, 2020). The different genotypes exhibited decreasing photosynthetic activity at elevated temperatures, which could be an important feature for the strength of the relationship between the symbiont and the host.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the NPP max of Symbiodinium linucheae SSA 01 was much lower in contrast to the other eight strains. This strain is also considered "heat tolerant" (Swain et al, 2017;LaJeunesse et al, 2018;Gegner et al, 2019) but might not be so beneficial for the coral host (Stat et al, 2008;Herrera et al, 2020). Although only minor photoinhibition was detected in the studied strains we cannot completely exclude an experimental effect as longer exposure to high irradiances could have resulted in a stronger photoinhibitory response.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One potential benefit of this strategy is the opportunity to partner with symbionts better suited to the local conditions in which a larva settles and develops. Horizontal transmission thus creates the opportunity for hosts to associate with a greater variety of symbionts, and the degree of flexibility in obligate nutritional symbioses has been subject to much research (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…These four individuals were all collected from more temperate regions in Japan and Australia, which had the lowest minimum annual temperatures of all locations surveyed ( Table 1 ). Temperature is a driving factor of the distribution of bacteria in the marine environment ( Sul et al, 2013 ), and has been shown to influence the symbiotic associations of other marine taxa, such as sepiolid squids ( Nishiguchi, 2000 ; Zamborsky and Nishiguchi, 2011 ) and cnidarians ( Herrera et al, 2020 ). Thus, the symbionts associated with these four specimens could have genetic adaptations to slightly cooler temperatures.…”
Section: Discussionmentioning
confidence: 99%